(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The main steps of rural policy to the development of renewable energy resources are energy crop production. Latvia can provide for the use of approximately 0.36 million ha of the unused now agricultural land for herbaceous energy crop growing. More than 230 million tones of peat are available for solid biofuel production. Peat is recomended as additive because it improves density and burning properties of herbaceous material solid biofuel. Herbaceous stalk material can be harvested in winter season with humidity less than 15% and used for compacting without drying. The aim of experimental investigation is to determine conditioning methods for solid biofuel production with minimum energy consumption. Common reed stalk material is used for experiments, because it experimentally stated ultimate tensile strength is 256 ± 27 N mm-2. This value testifies that common reeds are twice strongest material than cereal crop stalk materials and conditioning mechanization equipment of common reeds would be useful for other energy crops.